EJTM3 is also covering Mobility and Medicine at large, an update - Ugo Carraro (PAGEPress Publications, 2018)
Since the first 2018 issue, the European Journal of Translational Myology expanded its authorship and readership from the strict topics of biology, physiology, diagnostic, management and rehabilitation of skeletal muscle to the more clinically relevant fields of human mobility to those of general medicine. This third issue opens with a review on Chronic Fatigue Syndrome, a very complex medical problem, as its other names testify (Myalgic Encephalomyelitis or Systemic Exertion Intolerance Disease). A more typical molecular myology original article follows (Increasing autophagy does not affect neurogenic muscle atrophy), but then several Rapid Reports cover different Medical Specialties fields, related or unrelated to neuromyology, mobility problems and their potential solutions. The Advisors of EJTM invite Authors to submit typescripts, taking into account that the journal is keen to publish high-level papers in the fields of Translational Myology, Mobility and Medicine at large.